Using the Hierarchy Analysis Method when choosing dust cleaning equipment for foundry - V. Yu. Solomin; L. O. Shtripling (Омский научный вестник)
One of the most unfavorable operations in terms of dust affect in foundries of both conveyor type and serial and individual production is the knocking out of flasks. In these areas, the highest overall incidence among workers in the foundry is observed. To remove gases and dust from knock-out gratings, mechanical exhausts are installed, the dust-saturated air from which requires further dust cleaning before being released into the atmosphere. Cyclones are the most widely used in dust cleaning systems of such industries, but the choice of dust collectors is a nontrivial task and requires a systematic approach. This article discusses the method of selection and calculation of dust-cleaning equipment on the example of foundry dust based on the hierarchy analysis method.